Microfoundations for learning within international joint ventures - Park, Jeong-Yang; Harris, Simon (Elsevier, 2014)
IJV research highlights the importance of learning in international joint ventures (IJVs) but has not indicated how to achieve it. We combine organizational learning and internationalization process research within a microfoundations framework to understand learning in IJVs. We study a Samsung-Tesco IJV that successfully learned retail practice from one partner and applied it in a South Korean context known by the other. The managers used many learning processes, not just experiential learning emphasized in international business research, and used many more knowledge sources than assumed in prior research, including the IJV partners’ other subsidiaries. To build absorptive capacity, IJVs need appropriate microfoundations at individual, process and structural levels, and coherent interlinkages between them, especially by having IJV managers’ with extensive experience and orientation to learn who are given structural and process autonomy to invest in learning.